Fabrication And Properties Of Silica-Epoxy Thin Film Composite - Foo, Yin Lin Evon (2012)
With the increasing interest in high density electronics packaging, dimensional scaling becomes the key to evolution. In this study, epoxy thin film composites with silica fillers were fabricated using spin coating process. In the first part of this research, the mechanical and thermal properties of the thin film composites using micron-silica (µ-Si) and nano-silica (n-Si) fillers were compared. Low loading of n-Si thin film composites was found to have the ability to achieve equivalent tensile and thermal properties compared to the highly loaded µ-Si thin film composite. With higher surface area to volume ratio, n-Si shows its capability to achieve a substantial performance with-Si.